Need Analysis of Academic Supervision Instruments Based on TIRTA Coaching Model in Improving Teachers’ Performance - Arfin, Muhammad; Munirah, Munirah; Nurlina, Nurlina (PPSDP International Journal of Education, 2024)
This study aims to analyze the development and implementation of an academic supervision instrument based on the TIRTA Coaching model to improve teacher performance at SD Negeri 3 Kasimpureng, Bulukumba Regency. The research employs a Research and Development (R&D) method following the Borg and Gall model, consisting of ten stages from needs analysis to dissemination. Data were collected through interviews, observations, questionnaires, and documentation, and were analyzed using normality tests, homogeneity tests, and paired sample t-tests. The results revealed that the existing conventional and administrative academic supervision practices were insufficient in enhancing teacher motivation and the quality of learning. The developed TIRTA Coaching-based supervision instrument received expert validation and successfully underwent limited trials and operational testing, yielding positive outcomes. Teachers reported increased involvement in the supervision process, improved teaching performance, and more reflective and differentiated learning practices. The novelty of this study lies in the development of a TIRTA Coaching-based academic supervision instrument, tailored to the context of basic education and particularly supporting the implementation of the Independent Curriculum. This study contributes an alternative, collaborative, systematic, and practical supervision tool aimed at enhancing teacher professionalism and improving the quality of education at the school level.